COEVOLVING: A WAY WHEN A JUDGE BECOMES MORE THAN A JUDGE - Aprina Chintya (Judex Laguens, 2023)
Career development through professional organizations is the central concept in the importance of members joining professional organizations. As a professional organization, IKAHI need to accommodate and develop this professional organization into a strong organization that provides benefits to its members. Judges, however, not only carry out their main duties in examining and resolving cases, but are also bound by other additional duties. The question in this research is what are the strategies that can be carried out by IKAHI to make IKAHI an advanced professional organization? The following article presents a complementary and additional framework within developing and advancing the profession of judges, monitoring and expanding the field of movement of the profession, as well as gathering and providing opportunities for all members to work and play an active role in developing and advancing the profession. This framework is rooted in the theory of coevolving that integrates a responsive understanding of censure and relational responsibility, thus IKAHI become a professional organization that has advantages and collaborates with other organizations. The results of this study indicate that the strategy that IKAHI can take to make IKAHI an advanced professional organization is to carry out cross-organizational synergies through the concept of coevolving with counter-intuitive collaboration, developing competition, reducing concerns about efficiency, and respecting the personal interests of IKAHI members.